Seeding Rate Effects on Yield and Yield Components of Chickpea in South Dakota. Issue 1 (1st December 2013) - Nleya, Thandiwe; Rickertsen, John
Abstract : Chickpea ( Cicer arietinum L.) has recently been introduced to the semiarid regions of South Dakota. Kabuli type varieties targeted for the high value salad bar market dominate production in the state. Very little is known about the response of chickpea varieties to changes in management practices such as planting dates and fertilizer and seeding rates. This study was conducted at two locations in 2005 to 2006 to determine the effect of seeding rate on chickpea yield and yield components. The study had two kabuli chickpea varieties each year and six seeding rates ranging from 10 to 60 viable seeds/m 2 . Increasing the seeding rate increased seed yield at the two locations in both years. Optimum seeding rate for maximizing seed yield ranged from 40.6 to 52.5 seeds/m 2 depending on growing conditions. Harvest index was relatively constant at seeding rates above 20 seeds/m 2 . Chickpea plants compensated for low plant populations by producing more pods per plant although this was not enough to maintain high yield at low seeding rates in all environments. Seed weight decreased with increasing seeding rate suggesting that higher plant populations result in smaller seeds.